(untitled) (Research, Society and Development, 2021)
In order to evaluate the clinical response of brachycephalic dogs with stenosis of the nostrils submitted to rhinoplasty using the diode laser, 62 tutors of brachycephalic dogs with nostril stenosis were interviewed, questionnaires were applied in person. Thirty-two (51.6%) dogs were of the French Bulldog breed, 19 (30.6%) of the Pug breed, 6 (9.7%) were English Bulldogs and 5 (8.1%) were Shih tzus. Forty dogs (64.5%) were male and 22 (35.5%) female, with an average age of 29 months. Sleeping snoring was the most reported clinical sign, 62/62 (100%), followed by awake snoring, 57/62 (92%), exercise intolerance in 50 (80%), sleep apnea was reported in 30/62 ( 48%), and cyanosis in 21/62 (34%). Reverse sneezing, sneezing and coughing were cited in 49 (79%), 38 (61%) and 27 (43%) of those responsible, respectively. The survey also found that 82% (51/62) of the animals had flatulence, 80% (50/62) had choking, 74% (46/62) vomited, 71% (44/62) regurgitation and 29% (18 / 62) dysphagia. A marked reduction in clinical signs common to brachycephalic syndrome was found 30 days after performed the rhinoplasty using the diode laser, there was a 15% decrease in the occurrence of snoring while sleeping, 23% awake snoring, 22% exercise intolerance, 30% apnea, 48% reverse sneezing, 39% sneezing, 28% coughing and 28% cyanosis. Likewise, after surgery, there was a 14% decrease in the occurrence of flatulence, 41% of choking, 45% of vomiting, 39% in cases of regurgitation and 19% of dysphagia. The use of the diode laser proved to be effective in performing rhinoplasty in brachycephalic dogs with stenosis of the nostrils, promoting a reduction in clinical signs, with good aesthetic and functional results.